Penyuluhan Nutrasetikal Daun Sirih untuk Kesehatan Gigi dan Mulut di SDN 1 Ketewel, Gianyar - I Gusti Ayu Ari Agung; Dewa Made Wedagama; I Gusti Agung Ayu Hartini; Ni Putu Idaryati (Yayasan Literasi Sains Indonesia, 2023)
Betel leaf nutraceutical education for dental and oral health, especially for school age children, needs special attention because at this age children are undergoing the process of growth and development. Children's teeth will influence the development of dental health in adulthood. Considering that the nutraceutical advantages of betel leaves for dental and oral health have been known for generations, they are easy to obtain, delicious and very cheap. Through the outreach program, it is hoped that it can increase knowledge and raise awareness of the importance of maintaining healthy teeth and mouth. The aim of this counseling is to provide knowledge to children about the importance of betel leaf nutraceuticals for maintaining healthy teeth and mouth. This type of counseling uses face-to-face counseling methods directly in class, starting with a pretest, and at the end of the counseling a posttest. In this extension activity, participants were active in taking part in the extension, so that this activity ran well. So it can be concluded that betel leaf nutraceutical counseling increases students' knowledge of betel leaf nutraceuticals for dental and oral health.